Stocks of carbon and nitrogen and partitioning between above‐ and belowground pools in the Brazilian coastal Atlantic Forest elevation range - Vieira, Simone A.; Alves, Luciana F.; Duarte‐Neto, Paulo J.; Martins, Susian C.; Veiga, Larissa G.; Scaranello, Marcos A.; Picollo, Marisa C.; Camargo, Plinio B.; do Carmo, Janaina B.; Neto, Eráclito Sousa; Santos, Flavio A. M.; Joly, Carlos A.; et al. (Ecology and evolution, 2011)
We estimated carbon and nitrogen stocks in aboveground biomass (AGB) and belowground biomass (BGB) along an elevation range in forest sites located on the steep slopes of the Serra do Mar on the north coast of the State of São Paulo, southeast Brazil. In elevations of 100 m (lowland), 400 m (submontane), and 1000 m (montane) four 1‐ha plots were established, and above‐ (live and dead) and belowground (live and dead) biomass were determined. Carbon and nitrogen concentrations in each compartment were determined and used to convert biomass into carbon and nitrogen stocks. The carbon aboveground stock (CAGB) varied along the elevation range from approximately 110 to 150 Mg·ha−1, and nitrogen aboveground stock (NAGB), varied from approximately 1.0 to 1.9 Mg·ha−1. The carbon belowground stock (CBGB) and the nitrogen belowground stock (NBGB) were significantly higher than the AGB and varied along the elevation range from approximately 200–300 Mg·ha−1, and from 14 to 20 Mg·ha−1, respectively. Finally, the total carbon stock (CTOTAL) varied from approximately 320 to 460 Mg·ha−1, and the nitrogen total stock (NTOTAL) from approximately 15 to 22 Mg·ha−1. Most of the carbon and nitrogen stocks were found belowground and not aboveground as normally found in lowland tropical forests. The above‐ and belowground stocks, and consequently, the total stocks of carbon and nitrogen increased significantly with elevation. As the soil and air temperature also decreased significantly with elevation, we found a significantly inverse relationship between carbon and nitrogen stocks and temperature. Using this inverse relationship, we made a first approach estimate that an increase of 1°C in soil temperature would decrease the carbon and nitrogen stocks in approximately 17 Mg·ha−1 and 1 Mg·ha−1 of carbon and nitrogen, respectively. We estimated carbon and nitrogen stocks in aboveground biomass (AGB) and belowground biomass (BGB) along an elevation range in forest sites located on the steep slopes of the Serra do Mar on the north coast of the State of São Paulo, southeast Brazil. In elevations of 100 m (lowland), 400 m (submontane), and 1000 m (montane) four 1‐ha plots were established, and above‐ (live and dead) and belowground (live and dead) biomass were determined. Carbon and nitrogen concentrations in each compartment were determined and used to convert biomass into carbon and nitrogen stocks.